2006
DOI: 10.1007/s00701-006-0747-z
|View full text |Cite
|
Sign up to set email alerts
|

Cold as a therapeutic agent

Abstract: The use of cold as a therapeutic agent has a long and colorful history. The Edwin Smith Papyrus, the most ancient medical text known, dated 3500 B.C., made numerous references to the use of cold as therapy. Baron de Larrey, a French army surgeon during Napoleon's Russian campaign, packed the limbs in ice prior to amputations to render the procedures painless. In the early twentieth century, a neurosurgeon, Temple Fay, pioneered "human refrigeration" as a treatment for malignancies and head injuries. In 1961, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 23 publications
0
62
0
4
Order By: Relevance
“…The clinical application of cerebral hypothermia began with the pioneering work of neurosurgeon Temple Fay, in 1938, but the program was abandoned during the second world war 12 . From the 1950s, studies on profound cerebral hypothermia beginning.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of cerebral hypothermia began with the pioneering work of neurosurgeon Temple Fay, in 1938, but the program was abandoned during the second world war 12 . From the 1950s, studies on profound cerebral hypothermia beginning.…”
Section: Discussionmentioning
confidence: 99%
“…28–33°C) support neuroprotective safety in humans, during cardiac, kidney, and brain surgery. 814 Morales et al had demonstrated a direct reduction in neutrophils compared to non-cooled controls in RP histology supporting the reduction of inflammation hypothesis. 15 …”
Section: Discussionmentioning
confidence: 84%
“…Preclinical investigations have utilized a variety of clinically relevant TBI models in different species and genders to model brain injury and clarify primary and secondary injury processes that may be targeted by therapeutic interventions (Atkins et al, 2007; Atkins et al, 2010; Bregy et al, 2012; Chatzipanteli et al, 1999; Chatzipanteli et al, 2000; Rosomoff and Holaday, 1954; Wang et al, 2006). Based on preclinical work, it is known that TBI leads to a spectrum of secondary injury mechanisms including ionic fluctuations, excitotoxicity, necrosis and apoptotic cell death and inflammation.…”
Section: Introductionmentioning
confidence: 99%